Comparison of mental-physical comorbidity, risk of death and mortality among patients with mental disorders — A retrospective cohort study. (October 2021) - Tan, Xiao Wei; Lee, Eng Sing; Toh, Matthias Paul Han Sim; Lum, Alvin Wai Mun; Seah, Darren Ee Jin; Leong, Khai Pang; Chan, Christopher Yi Wen; Fung, Daniel Shuen Sheng; Tor, Phern Chern
Abstract: Aim: To compare the risk of death, the prevalence of comorbid chronic physical illness and mortality among an Asian population of patients with mental disorders. Methods: This was a retrospective data analysing of medical records of patients with schizophrenia, depression, anxiety, bipolar disorder, alcohol use disorder (AUD) or substance use disorder and the comorbid chronic physical illnesses. The hazard risk of death was calculated with Cox regression and compared between patients with and without comorbid chronic physical illness(es). Odds ratios of specific comorbid chronic physical illness were calculated with logistic regression and mean crude death rate was calculated for patients with different mental disorders. Results: A total of 56, 447 patients with mental disorders were included in the analysis. Compared to patients without comorbid physical illness, patients with mental-physical comorbidity were associated with a higher risk of death [2.36 (2.22–2.52); hazard ratio (95% CI)] and less estimated survival days [2157 (2142–2172) vs 2508 (2504–2513)]. Compared to other mental disorders, those with AUD had the highest prevalence of two or more comorbid chronic physical illnesses and associated with the highest odds of comorbid hypertension, diabetes mellitus, stroke, nephritis, chronic kidney disease, and cancer. The highest one-year crude death rate was similarly observed in patients with AUD. Conclusions: Mental-physical comorbidity was associated with a higher risk of death compared to patients with mental disorders only. The highest prevalence of mental-physical comorbidity and mortality were observed in patients with AUD. More attention and resources may be needed to tackle the burden of AUD. Highlights: Patients with mental-physical comorbidity were associated with a higher risk of death compared to patients without comorbid physical illness. Alcohol use disorder was associated with the highest odds of comorbid chronic physical illness and five-year mortality. More attention and resources may be needed to tackle the burden of alcohol use disorder and its associated medical and social health effects.